Designing a Digital Entrepreneurship Model for Women in Home-Based Businesses with a Grounded Theory Approach - Fariba Mesri Eisalo; Naser Seifollahi; Ghasem Zarei (زن در توسعه و سیاست)
Digital entrepreneurship is acknowledged as a novel concept in the business world, which pertains to utilizing opportunities provided by the internet, mobile technology, and new media. The primary goal of this investigation is to develop a digital entrepreneurship model that is tailored to the needs of women who operate home-based businesses. This research is applied in terms of purpose, qualitative in methodology, and employs the grounded theory approach of Strauss and Corbin. It is exploratory in nature. The statistical population of the research includes university professors and entrepreneurs who have established home-based businesses through social media and digital platforms and have over 5 years of work experience. In this study, purposive sampling and snowball sampling procedures were implemented. In-depth and semi-structured interviews were conducted with 14 individuals until theoretical saturation was attained. This was the data collection tool. Maxqda software was employed to analyze the interview transcripts, utilizing coding techniques and both manifest and latent content analysis. This process ultimately resulted in the presentation of a paradigmatic model.The findings indicate that entrepreneurial empowerment, technology, and individual factors serve as causal conditions, while opportunities, infrastructure, individual knowledge, and content serve as contextual factors. Internal factors and effective communication function as intervening conditions for digital entrepreneurship in home-based businesses. Proposed strategies include the potential of online advertising, specialized leadership and management, digital laws and regulations, and digital marketing strategies. The implementation of these strategies leads to the establishment of transnational networks, the creation of job value for women, and improved economic performance.